2012
DOI: 10.4103/0975-3583.102694
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume and other platelet volume indices in patients with stable coronary artery disease and acute myocardial infarction: A case control study

Abstract: Background:Coronary artery disease is mainly caused by atherosclerosis and its complications. Platelets and their activity have an important role in initiation of atherosclerotic lesions and coronary thrombus formation. Larger platelets are enzymatically and metabolically more active and have a higher potential thrombotic ability as compared with smaller platelets.Aims:To study the changes in platelet volume indices and platelet count in acute myocardial infarction, stable coronary artery disease and compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 19 publications
(12 reference statements)
3
48
1
7
Order By: Relevance
“…The Thrombus leads to partial or complete coronary artery occlusion which in turn leads to myocardial ischemia and various clinical manifestations ranging from unstable angina (UA) to acute myocardial infarction (AMI). 1,2 Platelets play a crucial role in pathogenesis of atherosclerotic complications, contributing to the thrombus formation after plaque rupture. 3,4 Increased platelet reactivity as well as shortened bleeding time is associated with increased platelet volume.…”
Section: Introductionmentioning
confidence: 99%
“…The Thrombus leads to partial or complete coronary artery occlusion which in turn leads to myocardial ischemia and various clinical manifestations ranging from unstable angina (UA) to acute myocardial infarction (AMI). 1,2 Platelets play a crucial role in pathogenesis of atherosclerotic complications, contributing to the thrombus formation after plaque rupture. 3,4 Increased platelet reactivity as well as shortened bleeding time is associated with increased platelet volume.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported platelet volume to be significantly higher among acute myocardial infarction patients than control subjects. 13,14 An elevated MPV correlates with poor clinical outcomes among survivors of myocardial infarction in the era of thrombolysis and an impaired response to thrombolysis in those with ST segment elevated myocardial infarction. 15 Elevated MPV has also been reported has also been reported to carry worse prognosis in terms of poor angiographic reperfusion and higher six months mortality following primary percutaneous coronary intervention (PCI) and also correlates with subsequent mortality and nonfatal myocardial reinfarction.…”
Section: Mean Platelet Volume As a Biomarker For Acute Myocardial Infmentioning
confidence: 99%
“…Few studies have shown that platelet volume indices vary between different ethnicities. [17], [18] Few medications, obesity, diabetes influence platelet indices. There is temporal increase in MPV values in EDTA anticoagulated sample.…”
Section: Jmscr Vol||4||issue||07||page 11189-11192||july 2016mentioning
confidence: 99%